Viscoelastic properties of self-consolidating concrete: Influence of the sustainable approach. (February 2018) - Samouh, Hamza; Rozière, Emmanuel; Bendimerad, Ahmed Zakarya; Loukili, Ahmed
Abstract: The service life of concrete structures is primarily affected by cracking. Concrete with a lower cracking potential is consequently more sustainable. In order to estimate the risk of shrinkage-induced cracking, at least four properties should be studied: shrinkage, Young's modulus, creep/relaxation and tensile strength. A mixed experimental and numerical approach, taking into account these properties is presented and used in this paper to improve our understanding of this complex phenomenon. The study is focused on restrained shrinkage of thin structures exposed to drying. Based on the viscoelastic and solidifying theories and on the experimental results from an adapted ring test some explanations of the observed cracking tendencies can be given. The efficiency of this method is shown when it is applied on two experimental studies linked with the sustainability issues. The first one concerns the greener mix-design which was found to have a positive effect on the cracking resistance, with two ways of reducing cement content. The reduction of the paste volume as well as the substitution of Portland cement by supplementary cementitious materials (SCMs) delayed cracking with different mechanisms. The second study aims to analyze the effect of the sealed curing duration on cracking, where the extracted aging-viscoelastic Young's modulus decreases with the curing duration and explains the observed results.